Desain Partisipatif Interior Ruang Rapat, Podcast, dan Pantry Kantor Desa Cimenyan, Kabupaten Bandung, Jawa Barat - Santri, Tyas; Aditya, Nova Chandra; Primasetra, Anjar; Pamungkas, Girhan Ramdan; Safaat, Firda (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
Cimenyan Village, located in Cimenyan Subdistrict, Bandung Regency, West Java, serves as a partner village for Langlangbuana University. The university's role involves collaborating with the village to address various local challenges. One such issue, as identified by village officials, is the absence of reference designs for the interiors of three new rooms in the Village Office building. To tackle this, a community service initiative titled